Trogocytic intercellular membrane exchanges among hematological tumors - LeMaoult, Joel (J Hematol Oncol, 2015)
Trogocytosis is the transfer of plasma membrane fragments and the molecules they contain between one donor and one acceptor/acquirer cell. Through trogocytosis, acceptor cells temporarily display and use cell-surface molecules they do not express themselves, but borrow from other cells. Here, we investigated whether liquid tumors possessed a trogocytic capability, if immune escape molecules could be acquired by tumor cells, transferred between cells of the same tumor, and if this could benefit the tumor as a whole. For this, we investigated trogocytosis in hematological cell lines and freshly isolated hematological tumor cells. We demonstrate that hematological tumor lines possess a trogocytic capability that allows them to capture membranes that contain the immune-inhibitory molecule HLA-G from allogeneic as well as from autologous sources. We further show that freshly isolated hematological tumor cells also possess these capabilities. This work reports for the first time the trogocytic capabilities of liquid tumor cells and introduces the notion of immune escape strategy sharing among tumor cells through trogocytosis of membrane-bound immune-inhibitory molecules. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13045-015-0114-8) contains supplementary material, which is available to authorized users.